Treasure Island - Laiken, Deidre S.; Stevenson, Robert Louis, 1850-1894. (New York : Baronet, 1977)
While going through the possessions of a deceased guest who owed them money, the mistress of an inn and her son find a treasure map that leads to a pirate fortune--and great danger.
7.0
5-8
5-8
Wilson's Children
Wilson's Junior High School
Keywords: Pirates -- Fiction; Buried treasure -- Fiction; Adventure and adventurers -- Fiction; Pirates -- Fiction; Buried treasure -- Fiction; Adventure fiction